РОЛЬ ЛЕЙКОЦИТАРНИХ ІНДЕКСІВ ПРИ ГОСТРОМУ КОРОНАРНОМУ СИНДРОМІ - Тащук, В. К.; Нестеровська, Р. А.; Полянська, О. С. (Українські медичні вісті, 2023)
РОЛЬ ЛЕЙКОЦИТАРНИХ ІНДЕКСІВ ПРИ ГОСТРОМУ КОРОНАРНОМУ СИНДРОМІ